2019
DOI: 10.1021/acsomega.9b00977
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Sustainable Bioderived Solvent (Biodiesel) for Phenol Extraction

Abstract: Replacement of volatile organic compound solvents by greener or more environmentally sustainable solvents is becoming increasingly important due to the increasing health and environmental concerns. In the present work, a bioderived solvent, soybean oil methyl ester, which is better known as biodiesel and is a nonvolatile organic compound, was used as a solvent to replace the fossil solvent (kerosene) for phenol extraction. First, biodiesel was selected as an optional solvent to replace kerosene based on Hansen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The enthalpy change of the extraction, ΔH, could be calculated from the slope of the lgD versus 1000/T by the Van’t Hoff Equation (2) [37,38]:lgD=ΔH2.303RT+C where R = 8.314 is the universal gas constant and C is a constant for the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enthalpy change of the extraction, ΔH, could be calculated from the slope of the lgD versus 1000/T by the Van’t Hoff Equation (2) [37,38]:lgD=ΔH2.303RT+C where R = 8.314 is the universal gas constant and C is a constant for the system.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding Gibbs free energy ΔG and entropy ΔS were calculated using Equations (3) and (4) [37], respectively, and their values were listed in Table 3. ΔG=RTlnKex ΔS=ΔHΔGT …”
Section: Resultsmentioning
confidence: 99%
“…Due to their polar nature, different solvents may give varied oil yields when using the solvent extraction process. Oil extraction solvents such as hexane, propane, ethane, tetrahydrofuran (THF), ethanol, dichloromethane, methanol, and the methanol-water binary system were all widely employed (Haile et al, 2019;Zhang et al, 2019;Alrashidi et al, 2020). Even if there is great purity and high oil production by utilising solvent, there is still energy squandered throughout the lengthy extraction process.…”
Section: Solvent-based Extraction (Soxhlet Extraction Method)mentioning
confidence: 99%
“…BRs were regenerated with an antiextraction method for four cycles without significant changes in separation efficiency and their properties. In addition, Yatong Zhang et al [45] used biodiesel to extract phenol, and results showed that phenol extraction efficiency reached 98%. However, the regeneration ability of the extractant was not further investigated.…”
Section: Study On Recyclability Of Natural Deep Eutectic Solventsmentioning
confidence: 99%